Bloomsbury dictionary of music - Morehead, Philip D. (Bloomsbury, 1992)
This dictionary contains over 10,000 entries, complemented by 200 line illustrations and musical examples, an extensive thematic bibliography and a glossary of muscial terms in four languages. Composers and musicians within this book range widely - from Palestrina to Puccini, Boulez to Beethoven, Led Zeppelin to Louis Armstrong, Stockhausen to Sinatra. The author has covered classical and popular music, jazz, opera, world music, rock, and country and western. There are entries listing and charting professional companies, performers, venues, orchestras, muscial organizations and choirs, rock musicians and groups, as well as clear and concise explanations of musical forms, compositional techniques, harmony, analysis, improvisation, orchestration and musicology. Operas and operettas, symphonies and concertos, arias and popular songs are also included.